Analysis Of Viral Marketing, Social Media Engagement and Religiosity On Online Crowdfunding Platforms - Hamidah Tussifah; Rahmah Mumtahanatul Insirah (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Crowdfunding has emerged as an innovative fundraising solution, leveraging digital technology and social media to connect donors with beneficiaries. This study investigates the influence of religiosity, social media engagement, and viral marketing on millennials’ online donation decisions in Jakarta. Religiosity, reflecting spiritual values that motivate donations, emerged as the dominant factor, encouraging contributions as acts of worship and moral responsibility. Social media engagement enhances participation through active interactions like sharing and commenting, while viral marketing supports trust-building with engaging and informative content. Using a quantitative approach, data were collected via an online Likert-scale questionnaire from 196 purposively sampled respondents and analyzed using SPSS version 25. Results show all three factors significantly influence donation decisions. This study highlights the importance of integrating spiritual values into online campaigns and utilizing creative communication strategies to foster donor trust and engagement, emphasizing the synergy between technology and social values for sustainable online donation platforms.